Covenant and world religions : Irving Greenberg, Jonathan Sacks, and the quest for orthodox pluralism /: Irving Greenberg, Jonathan Sacks, and the quest for orthodox pluralism. (2023) - Goshen-Gottstein, Alon
No abstract available